Study on the System of Heads of Administrative Organs Responding to Lawsuits based on China’s Reality: – An Analytical Study based on the Supreme Law Guidance Cases - Shen, Baojia (Transactions on Social Science, Education and Humanities Research, 2023)
The system of heads of administrative organs responding to lawsuits in courts has been a legal provision since the enactment of the Administrative Procedure Law of the People’s Republic of China in 2015. The system has been witnessed to facilitate the review of administrative procedure cases, being conducive to source management and social stability. However, the common phenomenon of “appearance but silence” and the disparities in implementation by local governments run contrary to the original intention of the system. This paper conducts a case study based on the official guidance cases, dedicated to realizing the perfection of the system.